Refinery Operations Optimization Research based on Units Processing Characteristics - Ming Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The operational stability and continuity are key production characteristics of actual refinery processing units, which plays important role to safe and efficient production. While few literatures have given a sufficient and comprehensive expression of such characteristics. In view of the  problem, this paper discussed  refinery operations optimization based on operational stability and continuity. The production characteristics were described by logic proposition though logic rules and expert experiences, and the optimization problem of refinery operations was formulated as a logic programming model with object of maximizing production profit. Finally, the proposed model was used to optimize operations of a actual refinery. Numerical results illustrate the model’s feasibility and efficiency. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4494